Comprehensively Deepening Reform and Governance Modernization: Theoretical Foundations, Intrinsic Compatibility, and Logic of Action - Lin, Yangzi (International Journal of Humanities and Social Science, 2026)
The study analyzes the theoretical essence of Marxist classics on party theory and social change, the experience and accumulated knowledge of governing the party and the country over the century-long development of the ruling structure in China, and the rich historical background of political systems and governance concepts in traditional Chinese culture. This analysis demonstrates the intrinsic connection between the comprehensive deepening of reform and the modernization of party governance. In terms of operational logic, the study emphasizes the principles of maintaining overall party leadership, adopting a people-centered approach, promoting reform and innovation, and implementing comprehensive governance practices. These principles are not only central to modernizing governance but also essential for ensuring effective and sustainable administration. They have significant implications for advancing modernization in the current era, fostering a well-functioning political system, and supporting long-term governance stability. By employing a method that combines literature analysis with theoretical reasoning and practical investigation, this study clarifies the theoretical origins of "advancing the modernization of party governance," deeply explores its key convergence points, and seeks the underlying logic of development. It maintains that upholding overall party leadership, a people-centered approach, reform and innovation, and comprehensive governance practices constitute the pathways for modernizing party and governmental governance in the context of comprehensive reform, offering theoretical guidance and practical reference for advancing governance modernization under current historical conditions.